2016
DOI: 10.1111/fog.12173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the behavior of skipjack (Katsuwonus pelamis), yellowfin (Thunnus albacares) and bigeye (T. obesus) tuna associated with drifting FADs in the equatorial central Pacific Ocean

Abstract: We evaluated the behavior of skipjack (Katsuwonus pelamis), yellowfin (Thunnus albacares) and bigeye tuna (T. obesus) associated with drifting fish aggregating devices (FADs) in the equatorial central Pacific Ocean. A total of 30 skipjack [34.5–65.0 cm in fork length (FL)], 43 yellowfin (31.6–93.5 cm FL) and 32 bigeye tuna (33.5–85.5 cm FL) were tagged with coded transmitters and released near two drifting FADs. At one of the two FADs, we successfully monitored the behavior of all three species simultaneously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
4
21
2
Order By: Relevance
“…Therefore, the maximum TRT of 55 days is likely underestimated. In any case, the values observed here for yellowfin and bigeye tuna are comparable to what was observed in other studies on anchored FADs (Dagorn et al, 2007a;Ohta and Kakuma, 2005;Rodriguez-Tress et al, 2017), but were never observed for drifting FADs (Dagorn et al, 2007b;Matsumoto et al, 2016;Schaefer and Fuller, 2010). It is also worth noting that these previously reported TRTs were calculated at the scale of an array of anchored FADs and not on a single drifting FAD, as in our study.…”
Section: Large-scale Association Dynamicssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the maximum TRT of 55 days is likely underestimated. In any case, the values observed here for yellowfin and bigeye tuna are comparable to what was observed in other studies on anchored FADs (Dagorn et al, 2007a;Ohta and Kakuma, 2005;Rodriguez-Tress et al, 2017), but were never observed for drifting FADs (Dagorn et al, 2007b;Matsumoto et al, 2016;Schaefer and Fuller, 2010). It is also worth noting that these previously reported TRTs were calculated at the scale of an array of anchored FADs and not on a single drifting FAD, as in our study.…”
Section: Large-scale Association Dynamicssupporting
confidence: 91%
“…Skipjack tuna did not remain associated with the FADs for such long periods and the maximum observed TRT for this species was 15 days. Most studies have observed that skipjack tuna generally associate with FADs for shorter periods of time, with reported maximum TRTs varying from 6.4 to 12.8days (Govinden et al, 2013;Matsumoto et al, 2016Matsumoto et al, , 2014. As an exception to this general finding, a skipjack tuna remained associated for a record of 40.9 days at an array of anchored FADs in Mauritius (Rodriguez-Tress et al, 2017).…”
Section: Large-scale Association Dynamicsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Chl-a front appears to coincide with the shelfbreak position (approximately 350 m isobath) of both Flores Sea and Bone Gulf (Figs 1 , 5 and 10 ). Highest skipjack CPUEs are concentrated near the shelfbreak location [ 17 ] during the daytime [ 55 ]. Our empirical fishing data (2007–2011) confirm that fishermen consistently exploit the forage habitat during the daytime and, using the fishing data in 2012, we showed that our prediction models have been substantially verified (Figs 5 , 8 and 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to concentrate on tuna species presence and abundance on DFADs, targeting depths below that occupied by the non-target species may be an effective strategy. Although tuna species could also be found at shallower depths and some by-catch species can have a partially overlapping vertical distribution during some hours of the day, studies using tag sensors have shown that tuna species generally remain deeper than non-target species [53,54]. The few studies that have assessed the presence of tuna at DFADs using echo-sounders have not considered data above 25 m to avoid targeting non-tuna species [51, 55].…”
Section: Discussionmentioning
confidence: 99%